Innovation, validity, and reliability of modified dynamic balance test for karate kata category - Wedi, S.; Tomoliyus; Fauzi; Gemaini, A.; Prabowo, T. A. (SportMont, 2024)
This study aims to create innovation through validity and reliability tests in the form of modification of dynamic balance test to meet the needs of karate athletes in kata category. The sample as a validation test was 11 experts from certified lecturers and coaches. Then, the sample as a reliability test was 50 male athletes with 10.5±8.3 years of karate training experience and 8.3±5.2 years of experience in the kata category, and 50 female athletes with 8.7±9.6 years of karate training experience and 7.7±8.4 years of experience in the kata category. The results of this study included seven aspects which were the suitability of the definition of balance to the test media, the suitability of the test specifically for the kata category, the appearance or design of images that are easy to understand, the test procedure that is easy to do, the distance at each cone, the ease to organize test, then validity value of Aiken V>0.8, reliability value of Cronbach`s Alpha 0.778 and ICC value 0.777, the results of the male and female athlete questionnaires through independent t-test (p